Air pollution exposure increases ABCB1 and ASCT1 transporter levels in mouse cortex - Puris, Elena; Saveleva, Liudmila; Górová, Veronika; Vartiainen, Petra; Kortelainen, Miika; Lamberg, Heikki; Sippula, Olli; Malm, Tarja; Jalava, Pasi I.; Auriola, Seppo; Fricker, Gert; Kanninen, Katja M. (Environmental toxicology and pharmacology, 2022)
Membrane transporters are important for maintaining brain homeostasis by regulating the passage of solutes into, out of, and within the brain. Growing evidence suggests neurotoxic effects of air pollution exposure and its contribution to neurodegenerative disorders, including Alzheimer’s disease (AD), yet limited knowledge is available on the exact cellular impacts of exposure. This study investigates how exposure to ubiquitous solid components of air pollution, ultrafine particles (UFPs), influence brain homeostasis by affecting protein levels of membrane transporters. Membrane transporters were quantified and compared in brain cortical samples of wild-type and the 5xFAD mouse model of AD in response to subacute exposure to inhaled UFPs. The cortical ASCT1 and ABCB1 transporter levels were elevated in wild-type and 5xFAD mice subjected to a 2-week UFP exposure paradigm, suggesting impairment of brain homeostatic mechanisms. This study provides new insight on the molecular mechanisms underlying adverse effects of air pollution on the brain.